The Urgency of Regulating Digital Inheritance to Protect the Distribution of Successive Rights in Indonesia - Nurjana Nurjana; Dolot Alhasni Bakung; Fitran Amrain (Yayasan Cerdas Pedia Indonesia, 2026)
The rapid commercialization of digital platforms necessitates recognizing digital assets as inheritable wealth. However, Indonesia currently lacks explicit regulations addressing digital inheritance under both civil and Islamic law, thus creating a profound juridical void. This normative legal research critically evaluates the legal standing of digital assets within national inheritance systems and assesses the urgency of specific protective regulations. Utilizing statutory and conceptual approaches, this study reveals that while digital assets conceptually qualify as intangible inheritable property, practical impediments regarding unauthorized access, complex ownership proof, and restrictive platform policies severely hinder successive rights distribution. Rooted in the responsive law theory, this paper ultimately concludes that enacting comprehensive digital inheritance legislation is critically urgent today. Establishing adaptive legal frameworks will guarantee absolute legal certainty, systematically facilitate secure asset transfers, successfully mitigate international jurisdictional disputes, and comprehensively protect the fundamental economic rights of all modern legitimate heirs across the entire Indonesian national jurisdiction.